Cancer Immunology - Subramanian, Subree; Zhao, Xianda (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The past decade has seen immunotherapy rise to the forefront of cancer treatment. This Special Issue of Cancers aims to elaborate on the latest developments, cutting-edge technologies, and prospects in cancer immunology and immunotherapy. Seventeen exceptional studies, including original contributions and review articles, written by international scientists and physicians, primarily concerning the fields of tumor biology, cancer immunology, therapeutics, and drug development, comprise the main body of this Special Issue.